Effects of granular shape on shear modulus and damping ratio of gravel - Kai Cui; Hang Sheng (Earth Sciences Research Journal)
The effects of the consolidation ratio, effective confining pressure, gravel content, and granule breakage on the shear modulus and damping ratio of gravel have been extensively researched in recent years. However, studies on the effect of the granular shape are rare. Thus, under different confining pressures, dynamic triaxial tests were performed on gravel specimens to investigate the effect of granular shape on the shear modulus and damping ratio of gravel specimens by using a multifunctional triaxial testing instrument. The samples consisted of two kinds of gravel with the same grain composition and relative density of 45%. The test results indicate that, when the confining pressure and shear strain amplitude exceed 300 kPa and 7×10-4, respectively, gravel with a round granular shape has a higher shear modulus compared to an angular shape. Conversely, when the shear strain amplitude exceeds 2×10-4, the damping ratio of angular gravel exceeds that of round granules.